2018
DOI: 10.3389/fpsyg.2018.00249
|View full text |Cite
|
Sign up to set email alerts
|

Acute Bouts of Exercising Improved Mood, Rumination and Social Interaction in Inpatients With Mental Disorders

Abstract: Background: Studies at the macro level (such as longer-term interventions) showed that physical activity impacts positively on cognitive-emotional processes of patients with mental disorders. However, research focusing on the immediate impact of acute bouts of exercise (micro level) are missing. The aim of the present study was therefore to investigate whether and to what extent single bouts of moderately intense exercise can influence dimensions of psychological functioning in inpatients with mental disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 90 publications
1
32
2
Order By: Relevance
“…Possible mechanisms for this effect include stress-reducing effects of information-sharing or co-rumination (talking through problems together with others) [ 43 , 44 ], positive mood contagion [ 45 , 46 ], and general mood-boosting effects of social interaction [ 47 , 48 ]. Although we found no strong evidence of a pathway between social media use, physical activity, and self-reported emotional valence in our emotion-reporting subsample, simulation evidence suggested we lacked power to determine absence of effects in this analysis, and a positive predictive association between physical activity and mood has been well-established in previous work [ 47 , 49 ]. Importantly, increased physical activity may activate a positive feedback loop, whereby greater activity improves mood and therefore further enhances motivation to continue exercising.…”
Section: Discussioncontrasting
confidence: 53%
“…Possible mechanisms for this effect include stress-reducing effects of information-sharing or co-rumination (talking through problems together with others) [ 43 , 44 ], positive mood contagion [ 45 , 46 ], and general mood-boosting effects of social interaction [ 47 , 48 ]. Although we found no strong evidence of a pathway between social media use, physical activity, and self-reported emotional valence in our emotion-reporting subsample, simulation evidence suggested we lacked power to determine absence of effects in this analysis, and a positive predictive association between physical activity and mood has been well-established in previous work [ 47 , 49 ]. Importantly, increased physical activity may activate a positive feedback loop, whereby greater activity improves mood and therefore further enhances motivation to continue exercising.…”
Section: Discussioncontrasting
confidence: 53%
“…Second, following Siengsukon et al (56), we anticipated that 3 weeks of regular exercise would improve their subjective sleep. Third, following others (10, 24, 57, 58, 67, 68), we hypothesized that 3 weeks of regular exercise would have a positive impact on depression, fatigue, and paresthesia among such patients. Fourth, in line with previous research (6971), we expected that a 3-week program of regular exercise would improve the cognitive performance of MS patients.…”
Section: Introductionmentioning
confidence: 94%
“…While prior investigations have suggested that one single exercise episode can have positive effects on patients' well-being ( 26 , 27 ), studies also show that repeated participation in exercise therapy has a clinically relevant impact on psychiatric patients' cardiorespiratory fitness levels ( 28 ). The latter is important because cardiorespiratory fitness is associated with lower risk for cardiovascular diseases and cardiovascular disease-related mortality ( 29 , 30 ), conditions to which patients with psychiatric disorders are particularly susceptible ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%